Influence of the Bilayer Composition on the Binding and Membrane Disrupting Effect of Polybia-MP1, an Antimicrobial Mastoparan Peptide with Leukemic T-Lymphocyte Cell Selectivity - dos Santos Cabrera, Marcia Perez [UNESP]; Arcisio-Miranda, Manoel; Gorjao, Renata; Leite, Natalia Bueno [UNESP]; de Souza, Bibiana Monson [UNESP]; Curi, Rui; Procopio, Joaquim; Ruggiero Neto, Joao [UNESP]; Palma, Mario Sergio [UNESP] (Amer Chemical Soc, 2012)
This study shows that MP-1, a peptide from the venom of the Polybia paulista wasp, is more toxic to human leukemic T-lymphocytes than to human primary lymphocytes. By using model membranes and electrophysiology measurements to investigate the molecular mechanisms underlying this selective action, the porelike activity of MP-1 was identified with several bilayer compositions. The highest average conductance was found in bilayers formed by phosphatidylcholine or a mixture of phosphatidylcholine and phosphatidylserine (70:30). The presence of cholesterol or cardiolipin substantially decreases the MP-1 pore activity, suggesting that the membrane fluidity influences the mechanism of selective toxicity. The determination of partition coefficients from the anisotropy of Tip indicated higher coefficients for the anionic bilayers. The partition coefficients were found to be 1 order of magnitude smaller when the bilayers contain cholesterol or a mixture of cholesterol and sphingomyelin. The blue shift fluorescence, anisotropy values, and Stern-Volmer constants are indications of a deeper penetration of MP-1 into anionic bilayers than into zwitterionic bilayers. Our results indicate that MP-1 prefers to target leukemic cell membranes, and its toxicity is probably related to the induction of necrosis and not to DNA fragmentation. This mode of action can be interpreted considering a number of bilayer properties like fluidity, lipid charge, and domain formation. Cholesterol-containing bilayers are less fluid and less charged and have a tendency to form domains. In comparison to healthy cells, leukemic T-lymphocyte membranes are deprived of this lipid, resulting in decreased peptide binding and lower conductance. We showed that the higher content of anionic lipids increases the level of binding of the peptide to bilayers. Additionally, the absence of cholesterol resulted in enhanced pore activity. These findings may drive the selective toxicity of MP-1 to Jurkat cells.